Analisis Kekeringan Menggunakan Metode Theory of Run pada Sub-sub DAS Riam Kanan Kalimantan Selatan - Munasipah Munasipah; Nurlina Nurlina; Ichsan Ridwan (Lambung Mangkurat University Press, 2019)
The drought is a routine problem that occurs at several region in Indonesia. Due to the drought, water depletion in the Riam kanan watershed sub-district is very large. Several methods are used to find out and analyze the drought that occurs, one of them is the Theory of Run method. The Theory of Run method is a method to calculate the drought index in the form of the longest duration and the largest number of droughts with a certain return period in some area. The results showed that the longest duration of drought occurred in 2009, for 12 months with the largest number of cumulative droughts was 1125 mm. Based on the drought level distribution map, Aranio Subdistrict was the worst region of drought. In 1998-2002, 2003-2007, 2008-2012, and 2013-2017 the area of drought reached 88,918.62 ha, 90,873.6 ha, all of the Aranio Subdistrict regions , and 69,710.34 ha, respectively.